Iskemia Tungkai Akut: Perspektif Baru pada Diagnosis, Pengobatan, dan Upaya Pencegahan Amputasi - Balqis, Fathinnisa Adillah; Ermawan, Romi; Nugraha, Gede Rama Hardy; Ragad, Putra; Dewi, Komang Puspa; Ramadhani, Dhea Asty; Rizky, Muhammad Ilham (Universitas Nurul Jadid, 2024)
Acute Limb Ischemia (ALI) is a medical emergency caused by a sudden decrease in blood flow to the extremities, often within less than two weeks. This review examines the definition, epidemiology, pathophysiology, clinical presentation, and management of ALI. The condition is primarily triggered by thrombosis or embolism in arteries previously affected by atherosclerosis. Characteristic symptoms include the